Need of Reforms of Indian Products due to Invasion of Chinese Products - Ahmed, Sarfraj (Journal of Commerce and Trade, 2012)
Come any occasion and the Indian consumer is ready to make a beeline to purchase another of those Chinese goods. For one, these Chinese goods are substantially cheaper than Indian goods and come in wide varieties. In very simple terms in Economics, we know that anything like large scale dumping and imports can spell a disaster for the economy. As the memory of an Indian consumer goes, this influx of cheap Chinese goods started in the late 90s and gained momentum thereon. Every article, be it an expensive Barbie doll or a painting you want to adorn your house with has a Chinese alternate to it. Why the Chinese goods are priced so cheap? The cost of production being less in China is an obvious answer but when we dwell deeper into the world of Chinese manufacturing, the reasons abound. Chinese goods are known for their moderate quality, prompt delivery and affordable prices in comparison to Indian goods.The Chinese entrepreneurs have infiltrated the market in a very systematic manner with their well-planned marketing strategies and continuous innovations. They study the demand patterns and the market trends and work out the lowest price that they can offer to attract a huge section of the consumers while still maintaining a profitable margin.